The Impact of Digital Media on Language Evolution in The 21st Century - Raj Kumar; Rohit Raj Sharma (Proceeding of the International Conference on Language, Literature, and Culture Studies, 2024)
The rapid development of digital media has significantly influenced the evolution of language in the 21st century. This study explores the impact of digital communication, including social media, memes, and online discourse, on linguistic changes such as neologisms, syntactic shifts, and informal language use. Using a sociolinguistic and discourse analysis approach, the findings of this study show that digital media accelerates language evolution by facilitating the rapid formation of new words and global linguistic trends.